The potencies of God(s) : Schelling's philosophy of mythology - Beach, Edward Allen, 1948- (SUNY series in philosophy., 1994)
This book explores the metaphysical, epistemological, and hermeneutical theories of Schelling's final system concerning the nature and meaning of religious mythology. This perspective is not surprising since Schelling regarded religion (not science or philosophy) as embodying the most complete manifestation of truth. Beach examines Schelling's novel attempt for the changing historical forms of religion in terms of a complex theory of dynamic spiritual powers, or "potencies." He shows that these are not mere representations, ideas, or projected feelings created by ancient myth-makers for the benefit of a credulous populace. Instead, Beach demonstrates that these potencies should be seen as animate powers inhabiting the unconscious strata of a people's collective mind